1982
DOI: 10.1002/bit.260240215
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen mass transfer into aerated CMC solutions in a bubble column

Abstract: Differing findings on the volumetric mass transfer coefficients k(L)a in CMC solutions in bubble column bioreactors have been reported in the literature. Therefore, oxygen mass transfer was studied again in CMC solutions in a 14-cm-i.d. x 270-cm-height bubble column using different spargers. The k(L)a values were determined along with the dispersion coefficients by fitting the prediction of the axial dispersed plug model with the experimental oxygen concentration profiles in the liquid phase. Surprisingly, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
66
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(77 citation statements)
references
References 13 publications
10
66
1
Order By: Relevance
“…This is in excellent agreement to the value obtained in three phase fluidized beds [10] where they have reported a value of 0.44. This is also in excellent agreement with the values obtained in bubble columns for non-Newtonian fluids [7,12,13] where values of 0.5, 0.44, and 0.5 have been reported. This dependence of k L a on U g is expected because an increase in U g causes an increase in gas holdup and therefore an increase of the specific gas-liquid interfacial area, a, hence the volumetric mass transfer coefficient, k L a, will increase.…”
Section: Effect Of Gas Velocitysupporting
confidence: 91%
“…This is in excellent agreement to the value obtained in three phase fluidized beds [10] where they have reported a value of 0.44. This is also in excellent agreement with the values obtained in bubble columns for non-Newtonian fluids [7,12,13] where values of 0.5, 0.44, and 0.5 have been reported. This dependence of k L a on U g is expected because an increase in U g causes an increase in gas holdup and therefore an increase of the specific gas-liquid interfacial area, a, hence the volumetric mass transfer coefficient, k L a, will increase.…”
Section: Effect Of Gas Velocitysupporting
confidence: 91%
“…Later, Rice and Littlefield (1987) reported that an ideal bubble flow (small uniform bubbles) was maintained at relatively high superficial gas velocities with a ''punctured rubber membrane'' in a bubble column giving minimal mixing. Deckwer et al (1982) measured the volumetric gasliquid mass transfer coefficient, k L a (per second), obtained with a ''rubber plate distributor'' made from a 2-mm-thick rubber sheet with 6.5 holes ⅐ cm −2 (needle diameter 0.3 mm) placed in a bubble column (14-cm inner diameter, 42-L liquid volume). The k L a (0.015 s −1 at superficial gas velocity v s ‫ס‬ 0.02 m ⅐ s −1 ; method: gassing-in N 2 in 0.7% CMC solution) of this construction was approximately twice the size of the value observed with perforated or sintered plates.…”
Section: Comparative Studiesmentioning
confidence: 99%
“…Deckwer et al (1982), using similar CMC solutions, observed that De increased as CMC concentration increased, but a correlation with viscosity was not made (concentrated CMC solutions generally behave as power law fluids). Since the dispersivity was so small, varying from a low of 1.9 to a high value of 8.5 cm3/s, one might conclude that the Taylor contribution arising from the term containing U*/K, must be quite small, since Geary and Rice (1992) demonstrated that circulation velocity varies as &, so U 2 should change significantly as Uo, increases (unless KE changes in the same way).…”
Section: High For Varying Viscosity Are Summarized Inmentioning
confidence: 89%
“…It is now becoming evident (Rice et al, 1981Deckwer et al, 1982; Rice and Littlefield, 1987;Geary and Rice, 1991) that the Flexisparger (elastic membrane sparger) has unique properties which produce highly uniform conditions leading to nearly ideal bubbly flow. Thus, under conditions of perfect vertical alignment, it has been demonstrated that bubble columns can be operated with minimum global circulation leading to low measured values of axial dispersion coefficient.…”
Section: Comments and Conclusionmentioning
confidence: 98%